Associations Between the Choroidal Vascularity Index and Malignant Glaucoma After Trabeculectomy for Primary Angle Closure Glaucoma - Zuo, Chengguo; Wang, Dingqiao; Guo, Xinxing; Xiao, Hui; Zheng, Shaoyang; Lin, Mingkai; Fang, Lei; Liu, Xing (Frontiers in Medicine, 2021)
Purpose: To compare choroidal vasculature characteristics using the choroidal vascularity index (CVI) in eyes with malignant glaucoma (MG), non-MG fellow eyes and eyes with uncomplicated primary angle-closure glaucoma (PACG) after trabeculectomy by spectral-domain optical coherence tomography (SD-OCT). Methods: This case-control study included 53 patients diagnosed with MG after trabeculectomy. Eyes with MG (n = 53) and the fellow eyes (n = 50) were included. Eyes with PACG without MG after trabeculectomy (n = 60) were also enrolled as controls. The choroidal parameters, including CVI and subfoveal choroidal thickness (SFCT), were measured using SD-OCT images. Results: Eyes with MG and the fellow eyes showed a significantly lower CVI than eyes of controls (all P < 0.001). After adjusting for age, sex, AL and intraocular pressure (IOP), eyes with a greater CVI (odds ratio [OR], 0.44) were significantly related to MG. The area under the receiver operating characteristic curve of the CVI was greater than that of the SFCT in the diagnosis of MG (0.911 vs. 0.840, P = 0.034). Conclusions: Eyes with MG showed a significantly lower macular CVI than PACG controls eyes. A higher macular CVI was an associated factor of MG eyes. The CVI serves as a more stable and sensitive indicator for MG than the SFCT in this group of patients with PACG.